Evidence That Speciation of Oxovanadium Complexes Does Not Solely Account for Inhibition of Leishmania Acid Phosphatases - Dorsey, Benjamin M.; McLauchlan, Craig C.; Jones, Marjorie A. (Frontiers in Chemistry, 2018)
Leishmaniasis is an endemic disease affecting a diverse spectra of populations, with 1.6 million new cases reported each year. Current treatment options are costly and have harsh side effects. New therapeutic options that have been previously identified, but still underappreciated as potential pharmaceutical targets, are Leishmania secreted acid phosphatases (SAP). These acid phosphatases, which are reported to play a role in the survival of the parasite in the sand fly vector, and in homing to the host macrophage, are inhibited by orthovanadate and decavanadate. Here, we use L. tarentolae to further evaluate these inhibitors. Using enzyme assays, and UV-visible spectroscopy, we investigate which oxovanadium starting material (orthovanadate or decavanadate) is a better inhibitor of L. tarentolae secreted acid phosphatase activity in vitro at the same total moles of vanadium. Considering speciation and total vanadium concentration, decavanadate is a consistently better inhibitor of SAP in our conditions, especially at low substrate:inhibitor ratios.